2022
DOI: 10.1200/jco.22.00754
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Racial and Ethnic Diversity in Cancer Clinical Trials: An American Society of Clinical Oncology and Association of Community Cancer Centers Joint Research Statement

Abstract: A concerted commitment across research stakeholders is necessary to increase equity, diversity, and inclusion (EDI) and address barriers to cancer clinical trial recruitment and participation. Racial and ethnic diversity among trial participants is key to understanding intrinsic and extrinsic factors that may affect patient response to cancer treatments. This ASCO and Association of Community Cancer Centers (ACCC) Research Statement presents specific recommendations and strategies for the research community to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
77
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 46 publications
(184 reference statements)
0
77
0
2
Order By: Relevance
“…While this program iteration focused on staff development, as a next step we see value in using the ER&R program resources to design workshops for investigators to help them identify and mitigate these barriers before study protocols and budgets are finalized. The Just Ask content itself is a component of the recently released joint recommendations by the American Society of Clinical Oncology and Association of Community Cancer Centers for increasing racial and ethnic EDI in cancer clinical trials [30,31]. The Just Ask Training Program has already been widely adopted and used for 75 cancer clinical research sites nationally, including academic centers and community clinics, and was found effective in building awareness and skills toward addressing inequities in clinical research participation [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this program iteration focused on staff development, as a next step we see value in using the ER&R program resources to design workshops for investigators to help them identify and mitigate these barriers before study protocols and budgets are finalized. The Just Ask content itself is a component of the recently released joint recommendations by the American Society of Clinical Oncology and Association of Community Cancer Centers for increasing racial and ethnic EDI in cancer clinical trials [30,31]. The Just Ask Training Program has already been widely adopted and used for 75 cancer clinical research sites nationally, including academic centers and community clinics, and was found effective in building awareness and skills toward addressing inequities in clinical research participation [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The Just Ask content itself is a component of the recently released joint recommendations by the American Society of Clinical Oncology and Association of Community Cancer Centers for increasing racial and ethnic EDI in cancer clinical trials [30,31]. The Just Ask Training Program has already been widely adopted and used for 75 cancer clinical research sites nationally, including academic centers and community clinics, and was found effective in building awareness and skills toward addressing inequities in clinical research participation [30,31]. Additionally, sponsors and agencies such as the NIH and FDA are taking crucial steps toward addressing barriers through policy and guidance for clinical studies conducted in partnership with, or funded by, them [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…There was also no association with race, however, it should be noted that these studies included predominantly white patients (77.5%). Lack of racial and ethnic diversity has been recognised as a deficiency of cancer clinical trials [12]. LTDFS≥10 years represents the proportion of patients who are likely cured and had an exceptional response to first line treatment in a relatively favorable subset of patients with Stage III ovarian cancer who had optimal debulking (based on definitions of optimal cytoreduction at the time of the trials) and met the eligibility criteria for inclusion in IP vs IV chemotherapy clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…4 In response, ASCO-Association of Community Cancer Centers recently published a joint research statement outlining recommendations for achieving equity, diversity, and inclusion (EDI) in CCTs. 5 The multifaceted nature of the recommendations addresses the complexity of the problem. These recommendations include education and training of the research teams to help them develop cross-cultural competencies, effective communication, and trustworthiness; routine evaluation of the site's performance and impact of the EDI goals; investment and engagement in programs, policies, and procedures that promote EDI and incorporate accountability mechanisms; inclusion of patients and communities as partners in the research process; investment in the hiring and development of a diverse workforce and programs that build capacity for supporting the enrollment of diverse populations in clinical trial research (such as navigators, ambassadors, and other clinical trial advocates); and finally, collection and sharing of EDI evidence and best practices.…”
mentioning
confidence: 99%